2011
DOI: 10.1007/s11095-011-0440-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating Peptide-Modified Block Copolymer Micelles Promote Direct Brain Delivery via Intranasal Administration

Abstract: We have demonstrated that utilization of nano-sized micelles modified with Tat can facilitate direct intranasal brain delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 14 publications
5
67
0
Order By: Relevance
“…The small particle size helped them to squeeze themselves through the small opening in the olfactory neurons to the brain via different endocystic pathways of neuronal cells in nasal membrane (Seju et al, 2011). Similar results were obtained by Kenazawa et al, where they reported that ZT and coumarin micelle nanocarriers can be delivered to the brain due to their ability to transport trans-cellulary through olfactory membrane (Kanazawa et al, 2011).…”
Section: Animal Studysupporting
confidence: 70%
“…The small particle size helped them to squeeze themselves through the small opening in the olfactory neurons to the brain via different endocystic pathways of neuronal cells in nasal membrane (Seju et al, 2011). Similar results were obtained by Kenazawa et al, where they reported that ZT and coumarin micelle nanocarriers can be delivered to the brain due to their ability to transport trans-cellulary through olfactory membrane (Kanazawa et al, 2011).…”
Section: Animal Studysupporting
confidence: 70%
“…39%, 5.78%, 144.25, 3.46, and 99.3, 70.07 for intranasal 99m Tc-PM7 and intranasal 99m Tc-CZ solution, respectively. These results are in accordance with Jain et al (2010) and Kanazawa et al (2011) who found that intranasal PM have a very high potential for brain targeting of zolmitriptan and coumarin, respectively.…”
Section: Biodistribution Studysupporting
confidence: 92%
“…The DTI values >1 could confirm the direct pathway from nose to brain (Wang, Jiang, Lu, 2003). These findings are in line with Jain et al (2010), Kanazawa et al (2011) who found that micellar nanocarriers of zolmitriptan and coumarin increase the nose-to-brain uptake, via the olfactory region of the nasal cavity. Finally, the higher value of DTI, DTE (%) and DTP (%) suggested that HP-SLNs have better brain targeting potential as compared to HP-Sol administered intranasally.…”
Section: In Vivo Studies For the Determination Of Pharmacokinetic And Bsupporting
confidence: 84%